2022
DOI: 10.21037/gs-21-848
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognostic index model for pancreatic cancer

Abstract: Background: Pancreatic cancer is a highly malignant tumor with poor prognosis. Chronic inflammation contributes to the progression of pancreatic cancer. However, few studies have examined the prognostic role of inflammatory markers in this cancer. Our study sought to analyze the prognostic risk factors of and construct a prognostic index (PI) model using inflammatory markers for pancreatic cancer.Methods: Forty-eight patients diagnosed with pancreatic cancer at our hospital were selected for this retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In contrast, inflammatory indexes that are easily derived from routine haematological parameters, particularly the NLR and the PLR, are increasingly studied in inflammatory states, including COPD, in view of their simple and rapid determination and easy interpretation. The potential role of both the NLR and the PLR in clinical practice is supported by their capacity to predict adverse outcomes in a wide range of disease states [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, inflammatory indexes that are easily derived from routine haematological parameters, particularly the NLR and the PLR, are increasingly studied in inflammatory states, including COPD, in view of their simple and rapid determination and easy interpretation. The potential role of both the NLR and the PLR in clinical practice is supported by their capacity to predict adverse outcomes in a wide range of disease states [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR), have been investigated in several disease states, e.g. solid tumours, systemic lupus erythematosus, coronary artery disease, retinal artery occlusion, chronic kidney disease and stable COPD [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that tumor invasion of large blood vessels causes tumor cells to form micro-metastases, and neovascularization provides nutrients for tumor growth, thus forming a vicious cycle [28]. Most studies have reported that the prognosis of pancreatic cancer patients with vascular invasion is poor [29]. However, there are few reports on the correlation between the invasion of different major peripancreatic vessels and the prognosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the pain symptoms of patients with unresectable pancreatic cancer may be relieved immediately after the treatment with HIFU 15 . In addition, previous studies have also confirmed that the tumor size, location, and patient serum markers of pancreatic cancer have a important clinical significance in predicting prognosis 16,17 …”
Section: Introductionmentioning
confidence: 90%
“…15 In addition, previous studies have also confirmed that the tumor size, location, and patient serum markers of pancreatic cancer have a important clinical significance in predicting prognosis. 16,17 Therefore, this study aimed at evaluate the relationship between these high-risk characteristics and prognosis of unresectable pancreatic cancer after HIFU treatment, in order to provide help for HIFU treatment of unresectable pancreatic cancer in the future.…”
Section: Introductionmentioning
confidence: 99%